Proteomic Study on the Reproductive Toxicity of Tripterygium Glycosides in Rats - Dai, Yanlin; Sun, Lihui; Han, Shanshan; Xu, Shanshan; Wang, Long; Ding, Ying (Frontiers in Pharmacology, 2022)
Tripterygium glycoside tablet (TGT) is a common clinically used and effective non-steroidal immunosuppressant. However, its reproductive toxicity limits its application in pediatric immune diseases, warranting the study of the molecular mechanism behind its reproductive toxicity. In the present study, 4-week-old male SD rats were provided TGT through continuous gavage with a clinically equivalent dose of 12 mg/kg for 12 weeks. The reproductive toxicity of TGT was recorded, and its toxicity mechanism was verified through experimental validation and proteomics analyses. Our results demonstrated that TGT could significantly reduce the testosterone level in the serum as well as the concentration and survival rate of sperms. Pathological sections of the testis revealed that TGT could reduce spermatocytes at different levels and make the convoluted meridians vacuolated. Based on TMT-labeled quantitative rats testicular tissue proteomics, 34 differential proteins were screened, involving protein digestion and absorption, PPAR signaling pathway, PI3K-Akt, and other pathways, among which PI3K-Akt plays an important role in the study of reproductive injury. Western blotting results revealed that TGT could significantly downregulate the Col1A1, Col1A2, p-PI3K, and p-Akt expressions and inhibit the expression of proteins related to the PI3K-Akt signaling pathway. In summary, the clinically equivalent dose of TGT induced reproductive toxicity of 4-week-old male SD rats, possibly in relation to the inhibition of the PI3K-Akt pathway expression.